Risk Factors of Infection in Total Knee Arthroplasty - Junaid Khan, Riaz Ahmed, Tehreem Zahid, Rahman Rasool Akhtar (Journal of Rawalpindi Medical College, 2017)
Background: To determine risk factors of infection in total knee arthroplasty Methods: In this descriptive study all patients undergoing primary total knee arthroplasty were included. Patients were followed post-operatively at 2,4,8,12 and 24 weeks. Signs of inflammation and inflammatory markers such as total leukocyte count (TLC), C-reactive protein (CRP) and ESR were measured. Risk factors like age, body mass index (BMI), ASA, co-morbid conditions were also noted. Results: Out of the 78 patients osteoarthritis (94.87%) was the pre-dominant cause of total knee replacement (TKR). 6.41% cases got infected. In majority of the infected cases (60%), Staphylococcus aureus was the infective organism. Diabetes Mellitus (p=0.01) and Obesity (p=0.02) had a significant relation to post-operative infection. Conclusion: Pre-operative risk evaluation and prevention strategies along with early recognition of infection and control can greatly reduce the risk of joint infection post-TKR which will not only improve the mobility of patient but also its morbidity and mortality as well